PENGGUNAAN BAHASA INDONESIA YANG BERDAMPAK HUKUM DI MEDIA SOSIAL TWITTER - Astuti, Andi; Salam, Salam; Sultan, Sultan (Universitas Negeri Makassar, 2024)
This study aims to describe: (1) the use of declarative speech acts in hate speech cases on Twitter social media. (2) describe the use of interrogative speech acts in cases of hate speech on Twitter social media. (3) describe the use of imperative speech acts in cases of hate speech on social media Twitter. This study uses a type of qualitative research with descriptive analysis. This study describes the use of declarative, interrogative, imperative speech acts in cases of hate speech on Twitter social media. Data collection techniques are carried out by capturing all the data and information needed by observing and capturing data, making the results of the analysis. This study uses research instruments, namely: the researcher acts as the main instrument and supporting instruments in the form of gadgets, laptops, and stationery. The results of the study reveal that in @dinadianne's uploads there are comments on the use of declarative speech acts in hate speech in this study in the form of words, phrases and sentences. The use of interrogative speech acts in the form of sentences. The use of imperative speech acts in the form of sentences.